A Study of the Values of Student Programmers in the Context of the Ideas of V.P. Tugarinov (to the 300th Anniversary of Saint Petersburg State University) - V. A. Glukhikh; R. E. Popov; A. A. Salakhutdinov; P. P. Deryugin (Дискурс)
Introduction. The article deals with the conceptual ideas of V.P. Tugarinov about the unity of knowledge and values, which reflect the integrity of knowledge – evaluation – practice. Within the framework of these theoretical guidelines, the results of an empirical study of the human capital of students are presented.Methodology and sources. The methodological foundations of the study are formed as a synthesis of ideas around the essential characteristics of values expressed by V.P. Tugarinov, provisions of the theory of human capital by G. Becker and methodological guidelines for the strategies of the sociological study of values by V.A. Yadov.Results and discussion. The first result is that students recognize a significant connection between the knowledge, skills and abilities acquired at the university with their system of values, which confirms the hypothesis about the relationship between human capital and personality values. The second result is that students-programmers mainly fix the role and importance of knowledge gained in the study of subjects of the socio-humanitarian cycle, which, in their opinion, play the role of a leading principle in the formation of a system of values. Conclusion. The conducted research shows the relevance of the modern reading of the conceptual ideas of V.P. Tugarinov regarding the connections of knowledge with values and further with productive activity. In the study, such connections are identified and characterized in a number of areas and content elements, it becomes obvious that any cognitive activity stimulates and develops the value system of students.